An oil leakage-proof high-barrier composite material for food packaging and a preparation method thereof
Patent Information
- Application Number
- CN202611329760.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-23
AI Technical Summary
但这类复合工艺多依赖物理附着或形成不可逆的共价界面结合,导致材料废弃后难以剥离为单一材质进行分类回收
本发明利用二硫键构建界面交联网络,包装使用期间结合牢固,废弃后经由还原剂处理,二硫键断裂,阻隔涂层与PE底材可高效分离,分离后的PE底材可作为单一材质直接回收再生利用,涂层组分亦可回收再利用,实现包装材料全生命周期闭环管理,解决传统复合材料依赖不可逆胶粘剂导致的回收难题。
Smart Images

Figure CN122958744A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of food packaging materials technology, and in particular to a high-barrier, leak-proof composite material for food packaging and its preparation method. Background Technology
[0002] With increasing demands for recycling and regenerating packaging waste, the application of general-purpose thermoplastic polymer packaging materials such as polyethylene (PE) in the packaging field is constantly expanding. However, these materials have significant shortcomings in their ability to block oxygen and oils, limiting their application in packaging high-oil and easily oxidized foods.
[0003] To improve barrier properties, existing technologies often employ multi-layered composite structures, such as introducing functional coatings like nano-clay or graphene oxide. However, these composite processes largely rely on physical adhesion or the formation of irreversible covalent interfaces, making it difficult to separate the materials into individual components for recycling after disposal. Some researchers have attempted to introduce acid- and base-sensitive dynamic covalent bonds (such as Schiff bases) to achieve on-demand separation, but real-world food environments (such as juices, salad dressings, and fermented foods) are often slightly acidic, potentially causing premature depolymerization of the packaging during use, leading to coating peeling and food safety risks.
[0004] Therefore, developing a composite packaging material that remains chemically stable under normal food contact conditions and can be effectively separated under specific recycling conditions is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0005] The purpose of this invention is to provide a high-barrier oil-proof composite material for food packaging. By introducing disulfide bonds (-SS-), the material can be separated and recycled as needed in environments containing reducing agents while ensuring stability in food contact environments.
[0006] In a first aspect, this application provides a high-barrier oil-proof composite material for food packaging, comprising a hydrophobic structural substrate layer and a high-barrier functional coating. The hydrophobic substrate layer is a polyethylene (hereinafter referred to as PE) film with a surface pretreated by grafting mercapto groups; The high-barrier functional coating is anchored to the mercaptoized surface of the hydrophobic structural substrate layer via dynamic covalent disulfide bonds; The high-barrier functional coating is formed by oxidative crosslinking and curing of a water-based coating containing thiolated chitosan, alkyl gallic acid ester modified graphene oxide, and a food-grade oxidation initiator.
[0007] In the composite system of this invention, thiol groups (-SH) are introduced into the substrate surface through plasma activation and grafting with a thiol silane coupling agent. The thiolized chitosan in the coating also contains free thiol groups. During the drying process after coating, a diluted food-grade oxidizing initiator (such as low-concentration hydrogen peroxide) promotes oxidative coupling of the thiol groups within the system, forming a high-density disulfide bond (-SS-) crosslinking network inside the coating and at the coating-substrate interface. The disulfide bonds exhibit good chemical stability at room temperature and in typical food acid and alkaline environments, maintaining the interfacial bonding strength and barrier properties of the packaging material during use. In the recycling stage, the waste material is placed in a solution containing a low-concentration environmentally friendly reducing agent (such as sodium dithionite or cysteine). The disulfide bonds undergo specific reduction and breakage, regenerating free thiol groups, which disintegrates the crosslinking network, thereby achieving separation of the coating from the substrate. PE substrate, as a single thermoplastic material, has a mature recycling and regeneration path. However, after the barrier coating is applied, the coating and the substrate are difficult to separate, which restricts its direct recycling and reuse. Through the dynamic disulfide bond interface design of this invention, the coating can be separated in the recycling stage, so that the PE substrate can be restored to a pure single material, which is convenient for direct entry into the recycling and regeneration process.
[0008] Preferably, the thickness of the hydrophobic structural substrate layer is 60μm~80μm; the dry film basis weight of the high-barrier functional coating is 2g / m³. 2 ~8g / m 2 Limiting the substrate thickness and coating weight aims to balance the mechanical strength, barrier properties, and cost of packaging materials.
[0009] Preferably, the thiolized surface of the hydrophobic substrate layer is treated with atmospheric pressure oxygen-containing plasma and then coated with a thiol-silane coupling agent that has undergone micro-acid pre-hydrolysis. Oxygen-containing plasma bombardment generates a large number of oxygen-containing polar groups (such as hydroxyl and carboxyl groups) on the PE film surface, which then undergo dehydration condensation with the coupling agent, which produces silanol groups (Si-OH) through micro-acid hydrolysis, forming a covalent anchor. This effectively solves the problem of low coating adhesion caused by the chemical inertness of the PE surface. Sufficient surface thiol density is a prerequisite for ensuring sufficient disulfide bond formation at the interface and achieving high bonding strength.
[0010] Preferably, the raw materials of the high-barrier functional coating include, by weight: 100 parts of thiolated chitosan, 2-10 parts of graphene oxide modified with alkyl gallic acid ester, 2000-5000 parts of aqueous acetic acid solution, and 0.5-3 parts of food-grade oxidation initiator.
[0011] Preferably, the raw materials for the high-barrier functional coating further include 3-8 parts of gallic acid as a crosslinking extender; the food-grade oxidation initiator is an aqueous solution of hydrogen peroxide with a mass fraction not exceeding 1%. Gallic acid molecules contain multiple phenolic hydroxyl groups, which can form a rich hydrogen bond network with thiolated chitosan and modified graphene oxide, increasing the system's density. Using diluted hydrogen peroxide as an oxidation initiator can gently catalyze the oxidation of thiol groups to disulfide bonds, avoiding excessive oxidation of thiol groups to sulfonic acid groups due to excessively high local concentrations.
[0012] Preferably, in the graphene oxide modified with alkyl gallate, the alkyl gallate is selected from octyl gallate, dodecyl gallate, or octadecyl gallate. Dodecyl gallate is preferred in this invention. The alkyl segments provide hydrophobicity, which helps reduce water absorption and swelling of the coating in high-humidity environments; the phenolic hydroxyl groups of the gallate form hydrogen bonds and π-π interactions with thiolated chitosan, promoting the uniform dispersion and orderly arrangement of nanosheets in the coating matrix, forming a dense brick-and-mortar layered labyrinth structure. A schematic diagram of the brick-and-mortar structure is shown below. Figure 3 As shown, this significantly extends the penetration pathways of oxygen and oil molecules.
[0013] Preferably, the gallic acid alkyl ester modified graphene oxide is obtained by a preparation method comprising the following steps: S1: Disperse monolayer graphene oxide in water to obtain an aqueous suspension of graphene oxide with a concentration of 2~10 mg / mL, and add ethanol to adjust the polarity of the system; S2: Add alkyl gallate to the system and sonicate at room temperature to anchor the alkyl gallate to the surface of the graphene oxide sheet through π-π conjugation and hydrogen bonding. S3: After ultrasonication, the mixture is centrifuged, washed, and redispersed in water to obtain the graphene oxide dispersion modified with alkyl gallic acid ester.
[0014] The above method is mild and environmentally friendly, avoids the use of organic solvents, and the resulting product has good dispersion stability in aqueous systems.
[0015] This invention also provides a method for preparing a high-barrier, leak-proof composite material for food packaging, comprising the following steps: (1) The hydrophobic structural substrate of polyethylene (PE) resin was activated by atmospheric pressure oxygen plasma and grafted with mercaptosilane coupling agent to obtain an active substrate with mercapto groups on the surface. (2) Dissolve thiolized chitosan in an aqueous acetic acid solution, and slowly add a dispersion of graphene oxide modified with alkyl gallate under strong stirring using a constant flow pump. Before coating, slowly add the food-grade oxidation initiator to obtain a water-based high-barrier coating. (3) The water-based high-barrier coating is applied to the thiolized surface of the active substrate; (4) Gradient temperature drying is carried out to evaporate the solvent and, under the catalysis of food-grade oxidation initiator, to promote the oxidative coupling reaction between the thiol groups of the thiolized chitosan in the coating and between the thiol groups of the chitosan and the thiol groups on the substrate surface, to form a disulfide bond cross-linking network. (5) The composite material is obtained by compacting and flattening with hot rollers.
[0016] Preferably, the volume fraction of the acetic acid aqueous solution in step (2) is 1%.
[0017] Preferably, the gradient temperature-controlled drying in step (4) includes, in sequence, a low-temperature zone of 40℃, a medium-temperature zone of 45℃-50℃, and a high-temperature zone not exceeding 55℃; the total drying time is 6-10 minutes, combined with high-volume airflow drying. The temperature is strictly controlled below the melting temperature of the substrate. The low-temperature zone facilitates the stable evaporation of moisture and the pre-orientation of the nanosheets; the medium-temperature zone accelerates the oxidative coupling reaction of disulfide bonds and solidifies the cross-linked network; the high-temperature zone completes the final drying. The high-volume airflow helps to quickly remove the evaporating moisture and improves the drying efficiency.
[0018] The beneficial effects of this invention are: This invention utilizes disulfide bonds to construct an interfacial cross-linking network, ensuring a strong bond during packaging use. After disposal, the disulfide bonds break through a reducing agent, allowing for efficient separation of the barrier coating from the PE substrate. The separated PE substrate can be directly recycled and reused as a single material, and the coating components can also be recycled and reused, achieving closed-loop management of the entire life cycle of packaging materials and solving the recycling problem caused by the reliance on irreversible adhesives in traditional composite materials.
[0019] This invention also significantly extends the penetration path by introducing gallic acid alkyl ester-modified graphene oxide to form a biomimetic brick-and-mortar layer structure within the coating. This is achieved at only 2-8 g / m³. 2 With a coating weight of [weight value], oxygen permeability is reduced, oil resistance is improved, and the packaging requirements for high-oil foods are met.
[0020] Furthermore, this invention employs a fully water-based coating system, eliminating the risk of solvent residue and migration. Through atmospheric pressure plasma and gradient temperature-controlled drying processes, it can be directly adapted to existing thin-film coating lines, achieving continuous production while avoiding thermal deformation of the substrate. Attached Figure Description
[0021] Figure 1 Here is a SEM image of the surface of the composite material obtained in Example 2; Figure 2 SEM image of the surface of the composite material obtained in Comparative Example 2; Figure 3 This is a schematic diagram of the brick-and-mortar structure of the cross-section of the composite material obtained in this invention. Detailed Implementation
[0022] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0023] Preparation Example 0 This preparation example provides a thiolized chitosan, and the specific preparation method is shown below: (1) Dissolve 2 g of N-acetyl-L-cysteine (NAC), 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC·HCl), and 1-hydroxybenzotriazole (HOBT) (molar ratio 4:1:1) in 10 mL of N,N-dimethylformamide (DMF) and stir continuously at room temperature for 3-6 hours to activate NAC.
[0024] (2) Chitosan (CS) was dissolved in 20% hydrochloric acid solution to prepare a polymer solution with a concentration of 1.25% (w / v).
[0025] (3) Add the activated NAC to the CS solution (the molar ratio of NAC to CS is 4:1), adjust the pH to 5 with NaOH, and react at room temperature in the dark for 3-6 hours.
[0026] (4) To purify the product and remove unreacted NAC, the reaction solution was dialyzed once with hydrochloric acid solution containing 5 mmol / L, twice with hydrochloric acid solution containing 1% NaCl (5 mmol / L), and then twice with hydrochloric acid solution containing 5 mmol / L. Each dialyzing time was 12 hours. All dialyzing processes were carried out at 4°C in the dark. The dialyzed solution was taken out, filtered through a 0.8 μm filter membrane to remove impurities, and then freeze-dried to obtain the final product.
[0027] Preparation Example 1: Preparation of graphene oxide modified with dodecyl gallate Measure 200 mL of commercially available (Sigma-Aldrich, catalog number 763705) aqueous dispersion of monolayer graphene oxide (GO) (concentration 2 mg / mL), and add 50 mL of ethanol to adjust the polarity of the system. Add 0.5 g of dodecyl gallate while stirring, and sonicate continuously for 1 hour at room temperature using an ultrasonic cell disruptor (300 W). This allows dodecyl gallate to spontaneously anchor to the surface of the graphene oxide sheets through π-π conjugation and hydrogen bonding. After sonication, centrifuge the mixture, wash the precipitate twice with deionized water to remove free modifier, and finally redisperse the precipitate in deionized water to obtain a dodecyl gallate-modified graphene oxide dispersion, denoted as AC-GO-12. Example 1
[0028] The preparation method of a high-barrier, leak-proof composite material for food packaging according to this embodiment includes the following steps: (1): A 60 μm thick PE film was used as a hydrophobic substrate and subjected to atmospheric pressure air plasma treatment (300 W power, 60 seconds) to introduce oxygen-containing polar groups on the surface. Mercaptopropyltrimethoxysilane (MPTMS, i.e., silane coupling agent KH-590) was dissolved in a mixed solvent of ethanol / deionized water (volume ratio 9:1) to prepare a 0.5% mass fraction solution. The pH was adjusted to 4-5 using glacial acetic acid, and the solution was pre-treated by hydrolysis at room temperature for 30 minutes to hydrolyze the methoxy groups of MPTMS to generate silanol groups (Si-OH). The pre-hydrolyzed solution was uniformly sprayed onto the surface of the plasma-treated film and dried and cured by hot air at 50 °C to allow the silanol groups to undergo dehydration condensation with the oxygen-containing polar groups on the substrate surface to form covalent anchoring and obtain an active substrate.
[0029] (2) Dissolve 100g of the thiolized chitosan obtained in Preparation Example 0 in 2000g of a 1% (v / v) aqueous acetic acid solution to obtain a matrix solution. Under the strong stirring of a high-speed shear disperser, slowly add 2g of AC-GO-12 obtained in Preparation Example 1 using a constant flow pump to avoid local charge imbalance causing polyelectrolyte flocculation, and add 3g of gallic acid as a crosslinking extender, and continue stirring for 30 minutes. Before coating, dilute a 30% (w / w) food-grade hydrogen peroxide aqueous solution with deionized water to below 1%, take 0.5g of the diluted solution, add it to the system slowly and stir evenly to avoid excessive local concentration causing the thiol groups to be over-oxidized to sulfonic acid groups, and finally obtain a homogeneous high-barrier coating.
[0030] (3) The coating is uniformly applied to the thiolized surface of the active substrate using a wire bar coater, and the wet film thickness is controlled so that the final dry film basis weight reaches 2 g / m². 2 .
[0031] (4) The coated film is fed into a high-volume, multi-stage drying tunnel, passing sequentially through a 40°C low-temperature zone, a 45°C medium-temperature zone, and a 55°C high-temperature zone. The total drying time is 6 minutes, with each zone lasting 2 minutes. The maximum drying temperature is 55°C, which is below the melting temperature of the PE substrate. This temperature accelerates the oxidative coupling of thiol groups catalyzed by hydrogen peroxide upon heating, while also preventing the film from deforming due to heat. During the drying process, hydrogen peroxide rapidly catalyzes the oxidative coupling of thiol groups upon heating, forming a disulfide bond cross-linking network.
[0032] (5) After drying, immediately use a mirror-finish hot roller at 40°C to compact and flatten the material, and then roll it up to obtain the target composite material. Example 2
[0033] The preparation method of a high-barrier, leak-proof composite material for food packaging according to this embodiment includes the following steps: (1) A 70 μm thick PE film was used as the substrate, and the same atmospheric pressure air plasma treatment and pre-hydrolysis MPTMS grafting process as in Example 1 was used to obtain the active substrate.
[0034] (2) Dissolve 100g of the thiolated chitosan obtained in Preparation Example 0 in 3000g of a 1% (v / v) aqueous acetic acid solution. Under strong shear stirring, slowly add 5g of AC-GO-12 obtained in Preparation Example 1 and 5g of gallic acid as a crosslinking extender using a constant flow pump, and continue stirring for 40 minutes. Before coating, dilute a 30% (w / v) food-grade hydrogen peroxide aqueous solution with deionized water to below 1%, take 1.5g of the diluted solution, add it to the system slowly dropwise and stir evenly to obtain a homogeneous high-barrier coating.
[0035] (3) The coating operation is the same as in Example 1, and the dry film weight is controlled to be 5 g / m².
[0036] (4) The drying process involves passing through a 40℃ low-temperature zone, a 50℃ medium-temperature zone, and a 55℃ high-temperature zone in sequence, combined with a large air volume for drying. The total drying time is 8 minutes, which is 3 minutes, 3 minutes, and 2 minutes respectively.
[0037] (5) The target composite material is obtained by compacting and winding with a 40℃ mirror hot roller. Example 3
[0038] The preparation method of a high-barrier, leak-proof composite material for food packaging according to this embodiment includes the following steps: (1) An 80 μm thick PE film was used as the substrate, and the same atmospheric pressure air plasma treatment and pre-hydrolysis MPTMS grafting process as in Example 1 was used to obtain the active substrate.
[0039] (2) Dissolve 100g of the thiolated chitosan obtained in Preparation Example 0 in 5000g of a 1% (v / v) aqueous acetic acid solution. Under strong shear stirring, slowly add an aqueous dispersion containing 10g of AC-GO-12 obtained in Preparation Example 1 using a constant flow pump, and add 8g of gallic acid as a crosslinking extender, and continue stirring for 60 minutes. Before coating, dilute a 30% (w / w) food-grade hydrogen peroxide aqueous solution with deionized water to below 1%, take 3g of the diluted solution, add it to the system slowly dropwise and stir evenly to obtain a homogeneous high-barrier coating.
[0040] (3) The coating operation is the same as in Example 1, and the dry film weight is controlled to be 8 g / m².
[0041] (4) The drying process is carried out in sequence through the 40℃ low temperature zone, the 50℃ medium temperature zone and the 55℃ high temperature zone, with a large air volume for drying. The total drying time is 10 minutes, which is 3 minutes, 4 minutes and 3 minutes respectively.
[0042] (5) The target composite material is obtained by compacting and winding with a 40℃ mirror hot roller.
[0043] Comparative Example 1 This comparative example uses a pure PE film without plasma activation and MPTMS grafting treatment as the substrate. The other coating formulations (thiolized chitosan, AC-GO-12, gallic acid, hydrogen peroxide, etc.), coating and drying processes are exactly the same as in Example 2.
[0044] Comparative Example 2 In the coating preparation process, no gallic acid alkyl ester modified graphene oxide dispersion was added, and the remaining components, substrate treatment, coating, and drying processes were exactly the same as in Example 2.
[0045] Actual test The composite materials prepared in the above embodiments and comparative examples were subjected to the following performance tests: I. Oxygen permeability: Tested according to GB / T 1038.1-2022 "Test method for gas permeability of plastic products films and sheets - Part 1: Differential pressure method" at 23℃ and 0% RH.
[0046] II. Oil Permeability: The test was conducted according to GB / T 16929-2025 "Test Methods for Oil Permeability of Packaging Materials". This standard specifies a general method for testing the oil permeability of packaging materials such as paper, plastic film, and composite materials. The principle involves bringing one side of the folded or uncfolded packaging material into contact with oil in a cotton pad and measuring the time required for the oil to permeate through the material. This test used uncfolded samples, commercially available refined vegetable oil, and a test temperature of 23℃±2℃. The oil-blocking performance of the material is expressed as the permeation time (h), with a longer permeation time indicating better oil-blocking performance. A total of 6 sample units were tested, and the arithmetic mean was taken.
[0047] III. Interface peel strength: Tested according to GB / T 8808-1988 "Peel test method for flexible composite plastic materials", with a sample width of 15 mm and a peel speed of 300 mm / min.
[0048] IV. Recovery Peel-off Rate: A 5cm × 5cm composite material sample was placed in a beaker containing 300mL of a 1% sodium dithionite aqueous solution and magnetically stirred at 50℃ for 30 minutes. After removal, the sample was rinsed with deionized water, and the percentage of the sample area where the coating was completely peeled off from the substrate was observed and calculated. The test results are shown in Table 1.
[0049] Table 1 Example 1 1.6 8 2.8 97.5 Example 2 1.2 9 3.2 97.7 Example 3 0.8 11 3.6 97.8 Comparative Example 1 4.0 3.5 0.8 99.8 Comparative Example 2 6.6 4 2.7 97.2 Examples 1-3 show that by introducing thiolized chitosan and forming a disulfide bond dynamic interface with the MPTMS-treated substrate, and combining it with a brick-mud barrier structure constructed using AC-GO, the schematic diagrams are shown below. Figure 3 As shown, excellent overall performance was achieved with low coating basis weight. With increasing coating thickness and AC-GO content, oxygen permeability decreased to 0.8–1.6 cm⁻¹. 3 / m 2 At 0.1 MPa for 24 hours, the oil penetration time was extended to 8-11 hours, indicating that the system can effectively prolong the penetration path. Comparative Example 1, lacking substrate thiolation pretreatment, could not form interfacial disulfide bonds, resulting in extremely weak interfacial adhesion and a peel strength of only 0.8 N / 15 mm. This poor adhesion was due to the lack of chemical bonding. Comparative Example 2, without the addition of AC-GO, saw an oxygen permeability increase to 6.6 cm⁻¹. 3 / m 2 • 24h • 0.1MPa, the oil penetration time was shortened to 4 hours, confirming that the layered brick-mortar structure of AC-GO plays an important role in blocking oxygen, grease, etc. Scanning electron microscopy was used to image the surfaces of the composite materials prepared in Example 2 and Comparative Example 2. Figure 1 and Figure 2As shown, the composite material prepared in Example 2 has a uniform and dense surface, while the composite material in Comparative Example 2 has poorer uniformity. This is because Example 2 added alkyl gallate, whose abundant hydrogen bonds and π-π interactions improve film formation and make the polymer chain network denser. It should be noted that the oxygen permeability data above are test results under laboratory conditions (23°C, 0% RH). In actual use environments (such as high humidity conditions), the GO nanosheets may swell slightly, and the barrier properties will fluctuate, but overall they can still meet the oxygen barrier requirements for packaging high-oil foods.
[0050] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A high-barrier, leak-proof composite material for food packaging, characterized in that, Includes a hydrophobic structural substrate layer and a high-barrier functional coating; The hydrophobic structural substrate layer is a polyethylene resin film with a surface pretreated by grafting mercapto groups. The high-barrier functional coating is anchored to the mercaptoized surface of the hydrophobic structural substrate layer via dynamic covalent disulfide bonds; The high-barrier functional coating is formed by oxidative crosslinking and curing of a water-based coating containing thiolated chitosan, alkyl gallic acid ester modified graphene oxide, and a food-grade oxidation initiator.
2. The composite material according to claim 1, characterized in that, The thickness of the hydrophobic substrate layer is 60μm~80μm; the dry film basis weight of the high-barrier functional coating is 2g / m³. 2~ 8g / m 2 .
3. The composite material according to claim 2, characterized in that, The thiolized surface of the hydrophobic structural substrate layer is treated with atmospheric pressure oxygen-containing plasma and then coated with a thiol silane coupling agent that has been pre-hydrolyzed by micro-acid.
4. The composite material according to claim 3, characterized in that, The raw materials of the high-barrier functional coating include, by weight: 100 parts of thiolated chitosan, 2-10 parts of graphene oxide modified with alkyl gallic acid ester, 2000-5000 parts of aqueous acetic acid solution, and 0.5-3 parts of food-grade oxidation initiator.
5. The composite material according to claim 4, characterized in that, The raw materials for the high-barrier functional coating also include 3 to 8 parts of gallic acid as a crosslinking extender; the food-grade oxidation initiator is an aqueous solution of hydrogen peroxide with a mass fraction of no more than 1%.
6. The composite material according to claim 1, characterized in that, In the graphene oxide modified with alkyl gallate, the alkyl gallate is selected from one of octyl gallate, dodecyl gallate, or octadecyl gallate.
7. The composite material according to claim 1, characterized in that, The gallic acid alkyl ester modified graphene oxide is obtained by a preparation method including the following steps: S1: Disperse monolayer graphene oxide in water to obtain an aqueous suspension of graphene oxide, and add ethanol to adjust the polarity of the system; S2: Add alkyl gallate to the system and perform ultrasonic treatment to anchor the alkyl gallate to the surface of the graphene oxide sheet through π-π conjugation and hydrogen bonding. S3: After ultrasonication, the mixture is centrifuged, washed, and redispersed in water to obtain the graphene oxide dispersion modified with alkyl gallic acid ester.
8. A method for preparing a high-barrier, leak-proof composite material for food packaging as described in any one of claims 1 to 7, characterized in that, Includes the following steps: (1) The hydrophobic structural substrate of polyethylene resin was activated by atmospheric pressure oxygen plasma and grafted with mercaptosilane coupling agent to obtain an active substrate with mercapto groups on the surface. (2) Dissolve thiolized chitosan in an aqueous acetic acid solution, and slowly add a dispersion of graphene oxide modified with alkyl gallate under strong stirring using a constant flow pump. Before coating, slowly add the food-grade oxidation initiator to obtain a water-based high-barrier coating. (3) The water-based high-barrier coating is applied to the thiolized surface of the active substrate; (4) Gradient temperature drying is carried out to evaporate the solvent and, under the catalysis of food-grade oxidation initiator, to promote the oxidative coupling reaction between the thiol groups of the thiolized chitosan in the coating and between the thiol groups of the chitosan and the thiol groups on the substrate surface, to form a disulfide bond cross-linking network. (5) The composite material is obtained by compacting and flattening with hot rollers.
9. The preparation method according to claim 8, characterized in that, The volume fraction of the acetic acid aqueous solution mentioned in step (2) is 1%.
10. The preparation method according to claim 8, characterized in that, The gradient temperature control drying in step (4) includes: a low temperature zone of 40℃, a medium temperature zone of 45℃-50℃ and a high temperature zone of no more than 55℃; the total drying time is 6min~10min, and it is combined with large air volume drying.